General practitioners' explanation and advice on childhood eczema and factors influencing their treatment strategy: A qualitative study - Halewijn, Karlijn F.; Warendorff, Tessa; Bohnen, Arthur M.; Veen, Mario; Pasmans, Suzanne G. M. A.; Bindels, Patrick J. E.; Elshout, Gijs (Skin health and disease, 2022)
Background Atopic dermatitis (AD) is common in children and the majority of children can be treated by the general practitioner (GP). Various factors can influence the GP's treatment strategy and may lead to less effective treatment. The objective is to gain insight into the treatment goal, treatment strategy, explanation and advice given by GPs when dealing with AD in children and to explore which factors play a role in the choice of pharmacological treatment. Methods Semi‐structured interviews in primary care in the Netherlands were audio‐recorded and transcribed. All data were analysed according to the six‐steps approach of inductive thematic analysis. Results We interviewed 16 GPs. Treatment goals mainly focussed on the short term. GPs discussed the importance of emollient use and emphasised emollients as the basis of treatment. We found that several factors played a role in prescribing topical corticosteroids (TCS); severity of the AD, age of the child, skin type, corticophobia among parents and GPs, experience of side effects and dermatological experience. GPs reported giving limited advice about the use of TCS and prescribed medication that is not recommended by the guideline. Conclusion Various factors seem to influence GPs' treatment strategy for AD in children. More attention and education about the use and safety of TCS in children during GP training, continuous medical education, probably improve treatment in line with guidelines and can lead to more confidence and knowledge about TCS among GPs, which ultimately may improve the education and self‐management of patients.